BIOMECHANICAL AND HYGIENIC ASPECTS OF FACIAL MASSAGE, RISKS AND HOW TO MINIMIZE THEM (Modern American Journal of Medical and Health Sciences, 2025)
This paper examines a number of biomechanical and hygienic aspects of facial massage, which are common methods of cosmetology and preventative treatment. Based on an analysis of the anatomical and physiological characteristics of the skin, muscle, and connective tissue, the nature of the mechanical effects of massage techniques is substantiated. The influence of massage on microcirculation, lymphatic drainage, and the functional state of facial muscles is examined.The key hygiene requirements for the procedure are covered, including skin preparation, compliance with sanitary standards, selection of cosmetics, and organization of massage conditions. The main risks associated with improper technique and violation of hygiene standards are discussed, including skin damage, vascular disorders, and infectious and allergic complications.